2004
DOI: 10.1192/bjp.184.1.41
|View full text |Cite
|
Sign up to set email alerts
|

Antidepressant-related deaths and antidepressant prescriptions in England and Wales, 1998–2000

Abstract: The efficacy and safety of augmentation therapy with TCAs in SSRI-resistant patients should be monitored carefully, and patients prescribed antidepressants should be screened for drug use/misuse.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
59
0
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 269 publications
(64 citation statements)
references
References 24 publications
3
59
0
2
Order By: Relevance
“…Both indices were significantly greater than that for citalopram, which in turn had a significantly higher mortality index than sertraline. Prior reports, based on comparisons with prescriptions written, have suggested there is greater mortality associated with venlafaxine overdose than with SSRIs (35)(36)(37). Alternatively, Rubino and colleagues (38) found that venlafaxine was more likely to be used in patients who exhibited factors suggesting greater suicidal risk and that adjusting for those factors reduced mortality risk.…”
Section: Discussionmentioning
confidence: 99%
“…Both indices were significantly greater than that for citalopram, which in turn had a significantly higher mortality index than sertraline. Prior reports, based on comparisons with prescriptions written, have suggested there is greater mortality associated with venlafaxine overdose than with SSRIs (35)(36)(37). Alternatively, Rubino and colleagues (38) found that venlafaxine was more likely to be used in patients who exhibited factors suggesting greater suicidal risk and that adjusting for those factors reduced mortality risk.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing fatal poisonings due to drugs has been documented in many studies (40)(41)(42)(43)(44)(45). The distribution of drugs causing fatal poisonings varies depending on the region.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, a number of large epidemiological reviews in the UK and Finland have suggested that venlafaxine is associated with more deaths per written prescriptions than other SSRIs suggesting a greater inherent toxicity [3][4][5][6]. It is difficult to determine from these large studies whether this is a true toxic effect or one related to the possibility that venlafaxine is prescribed to patients at higher suicidal risk than those prescribed SSRIs [7].…”
Section: Introductionmentioning
confidence: 99%